FORMULASI DAN UJI AKTIVITAS KRIM ANTI AGING EKSTRAK DAUN SIRIH (Piper betle L.) DENGAN VARIASI KONSENTRASI GLISERIN DAN PROPILEN GLIKOL PADA KULIT PUNGGUNG KELINCI PUTIH NEW ZAELAND - Wicaksono, Salsabila Melia Putri; Ekowati, Dewi; Handayani, Sri Rejeki (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Aging is a natural event of living things caused by extrinsic factors, one of which is ultraviolet light. Aging causes human skin to become wrinkled. In this study, the formulation of an anti-aging cream preparation of betel leaf extract (Piper betle L.) and the anti-aging activity test on the back skin of white rabbits in New Zaeland will be carried out. In previous studies, researchers used extraction using methanol as a solvent. This study aims to determine the healing of wrinkles on the back skin of rabbits due to exposure to UV-A rays. The extraction method used is the maceration method. Betel leaf extract was tested for water content and chemical content. The betel leaf extract was made into a cream formulation and then tested for the physical quality of the cream, namely organoleptic, cream type, homogeneity, pH, spreadability, adhesion, viscosity, and stability. Primary and ocular irritation test and anti-aging activity test were perfomed on the backs of 5 rabbits with 5 treatments. The skin on the rabbit’s back was smeared with negative control cream, positive control cream, betel leaf extract cream with variations of glycerin 5% propylene glycol 15%, glycerin 10% propylene glycol 10%, glycerin 15% propylene glycol 5%. The results of the study obtained that the yield of betel leaf extract was 12.04%. For stability results on cream of betel leaf extract, it was found that all physical quality tests were stable. The results of the irritation test using the Draize method showed that the betel leaf extract cream did not irritate the skin. Anti-aging activity test showed that betel leaf extract cream with various concentrations of glycerin 10% propylene glycol 10% and glycerin 5% propylene glycol 15% was the most effective in reducing wrinkles on the rabbit’s back skin